Controlling growth of poly (Triethylene glycol acrylate-co-spiropyran acrylate) copolymer liquid films on a hydrophilic surface by light and temperature - Ben-Miled, Aziz; Nabiyan, Afshin; Wondraczek, Katrin; Schacher, Felix H.; Wondraczek, Lothar (Polymers, 2021)
A quartz crystal microbalance with dissipation monitoring (QCM-D) was employed for in situ investigations of the effect of temperature and light on the conformational changes of a poly (triethylene glycol acrylate-co-spiropyran acrylate) (P (TEGA-co-SPA)) copolymer containing 12–14% of spiropyran at the silica–water interface. By monitoring shifts in resonance frequency and in acoustic dissipation as a function of temperature and illumination conditions, we investigated the evolution of viscoelastic properties of the P (TEGA-co-SPA)-rich wetting layer growing on the sensor, from which we deduced the characteristic coil-to-globule transition temperature, corresponding to the lower critical solution temperature (LCST) of the PTEGA part. We show that the coil-to-globule transition of the adsorbed copolymer being exposed to visible or UV light shifts to lower LCST as compared to the bulk solution: the transition temperature determined acoustically on the surface is 4 to 8 K lower than the cloud point temperature reported by UV/VIS spectroscopy in aqueous solution. We attribute our findings to non-equilibrium effects caused by confinement of the copolymer chains on the surface. Thermal stimuli and light can be used to manipulate the film formation process and the film’s conformational state, which affects its subsequent response behavior.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Dual-stimuli-responsive materials; Out-of-equilibrium; Thin films